2020
DOI: 10.1111/1365-2664.13605
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating foundation species: The potential for plant–bivalve interactions to improve habitat restoration success

Abstract: Vegetated marine and freshwater habitats are being increasingly lost around the world. Habitat restoration is a critical step for conserving these valuable habitats, but new approaches are needed to increase restoration success and ensure their survival. We investigated interactions between plants and bivalves through a review and analysis of 491 studies, determined the effects, mechanisms and key environmental variables involved in and driving positive and negative interactions, and produced guidelines for in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
74
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 83 publications
(92 citation statements)
references
References 241 publications
11
74
0
1
Order By: Relevance
“…In addition to industrial development, the scale of overfishing of oysters around the United Kingdom cannot be ignored as a fundamental change and major disturbance to the environmental conditions. There is growing evidence of the close positive interactions that occur between seagrasses and many bivalves ( Perkins, 1988 ; Gagnon et al, 2020 ). Locations such as the Firth of Forth have entirely lost up to 5,000 ha of oyster beds ( Thurstan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to industrial development, the scale of overfishing of oysters around the United Kingdom cannot be ignored as a fundamental change and major disturbance to the environmental conditions. There is growing evidence of the close positive interactions that occur between seagrasses and many bivalves ( Perkins, 1988 ; Gagnon et al, 2020 ). Locations such as the Firth of Forth have entirely lost up to 5,000 ha of oyster beds ( Thurstan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that promoting facilitative interactions between important species can increase the success of the ecosystem restoration (Derksen‐Hooijberg et al., 2017; Gagnon et al., 2020). Our results suggested a reciprocal facilitation between annual saltmarsh plants and burrowing crabs in the middle‐elevation saltmarshes of the Yellow River Delta, that the crabs facilitated plant seed retention and seedling establishment in winter and spring by modifying the sediment microtopography and the plants facilitated the crabs by providing protection from predators, providing food and reducing physical stresses in summer and autumn.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of restoration or habitat creation efforts, our findings suggest that harnessing self‐facilitation and mutualisms can enhance the success of such interventions to regain foundation species and their ecological benefits (Gagnon et al., 2020; Valdez et al., 2020). Indeed, recent experimental work in salt marshes highlights that including self‐facilitation into restoration designs by clumping cordgrass transplants rather than planting them in dispersed arrays can double restoration yields (Silliman et al., 2015).…”
Section: Potential Management Implicationsmentioning
confidence: 90%